Listen to the Earth, Listen to the Mother: Sebuah Usaha Ekofeminis untuk Merespons Rintihan Bumi - Agustina Samosir; Ejodia Kakunsi (Indonesian Journal of Theology, 2022)
Harm done to the environment and violence perpetrated against women prove to be entangled realities, insofar as both women and nature suffer interlocking experiences of exploitation and oppression. Movements advocating for women’s rights to an improved quality of life are inextricably linked with the survival of the earth itself, thereby birthing notions of ecofeminism that thematically center environmental conservation as emblematic of widespread struggle. In our paper, we show how women’s movements in various parts of the world—such as the indigenous peoples of Indonesia—emerge from a sense of responsibility to nature as well as affective commitments to sustain life. The breadth of Western, Latin American, and South Asian Indian (and other Asian) ecofeminist thought—from Sallie McFague, Rosemary Radford Ruether, and Elisabeth A. Johnson, to Ivone Gebara, Aruna Gnanadason, and others—are manifest in the philosophical notion of the motherland. The very concept of Mother Earth begets a personification of “Indonesian Earth” (bumi Indonesia) wherein nature becomes both subject and source of life. Reinforcing such a personification is our reading of Job 12:7-10, which instructs humankind to hear and learn from nature in order to gain wisdom. Our construction of an ecofeminist theology will inform, in turn, the protection of nature.